KEKERASAN DALAM DISKURSUS FILSAFAT MORAL - Moh. Fachri (JURNAL AT-TURAS, 2018)
Human being is the intelligent animals. With his mind human can determine and consider his choices on his deed. Likewise his conscience, man can guide and control his actions what he will do. In his life men has the good, last, highest. Purpose. That is the happiness. The perfect happiness that human wishes. In fact, human being always did the action that contradicted with his humanity. That is, doing “violence”. For this reason, we arrange this paper to find the illustration; how do the human being do his actions and deeds? and what do become the factors of the happening violence? This article uses many relevant theories, especially, morality and violence theories. Based on the discussion analysis above, it argues that the human deed is the humanity characteristic. It means that human does the action and he/she is responsible to those actions. But if she/he does not want to do the actions, she/he will not be responsible to those actions. The actions that is done arise from a certain motive, including to the happening of violence which is carried by the certain motive. It means that the different motive is based on different kind of violence. Finally, unfunctional mind like as usual, and the blunt of inner feeling cause the arisings of violence.